(sin^{μ-1}x-sin^{v-1}x)/cosx[0,π/2]などの定積分

\begin{alignat}{2}
&(1) \displaystyle\int_0^{\frac{π}{4}} (\sin^{μ-1} 2x-\sin^{v-1} 2x)\tan \left(\frac{π}{4}+x\right)dx=\frac{1}{2}\{ψ(v)-ψ(μ)\}\\
&(2) \displaystyle\int_0^{\frac{π}{4}} (\cos^{μ-1} 2x-\cos^{v-1} 2x)\cot xdx=\frac{1}{2}\{ψ(v)-ψ(μ)\}\\
&(3) \displaystyle\int_0^{\frac{π}{2}}\frac{\sin^{μ-1}x -\sin^{v-1} x}{\cos x}dx=\frac{1}{2}\left\{ψ\left(\frac{v}{2}\right)-ψ\left(\frac{μ}{2}\right)\right\}\\
&(4) \displaystyle\int_0^{\frac{π}{2}}\frac{\cos^{μ-1}x -\cos^{v-1} x}{\sin x}dx=\frac{1}{2}\left\{ψ\left(\frac{v}{2}\right)-ψ\left(\frac{μ}{2}\right)\right\}
\end{alignat}ただし、全て \(μ,v \gt 0\)










<証明>

\((1)\) \(\sin 2x=t\) と置きます。\((2 \cos 2xdx=dt)\)
\begin{alignat}{2}
&  \displaystyle\int_0^{\frac{π}{4}} (\sin^{μ-1} 2x-\sin^{v-1} 2x)\tan \left(\frac{π}{4}+x\right)dx\\
&=\displaystyle\int_0^1 (t^{μ-1}-t^{v-1})\sqrt{\frac{1+t}{1-t}}\cdot \frac{1}{2\sqrt{1-t^2}}dt\\
&=\frac{1}{2}\displaystyle\int_0^1 \frac{t^{μ-1}-t^{v-1}}{1-t}dt=\frac{1}{2}\{ψ(v)-ψ(μ)\}\\
\end{alignat}以上より$$\displaystyle\int_0^{\frac{π}{4}} (\sin^{μ-1} 2x-\sin^{v-1} 2x)\tan \left(\frac{π}{4}+x\right)dx=\frac{1}{2}\{ψ(v)-ψ(μ)\}$$









\((2)\) \(\cos 2x=t\) と置きます。\((-2 \sin 2xdx=dt)\)
\begin{alignat}{2}
&  \displaystyle\int_0^{\frac{π}{4}} (\cos^{μ-1} 2x-\cos^{v-1} 2x)\cot xdx\\
&=\displaystyle\int_1^0 (t^{μ-1}-t^{v-1})\sqrt{\frac{1+t}{1-t}}\cdot \left(-\frac{1}{2\sqrt{1-t^2}}\right)dt\\
&=\frac{1}{2}\displaystyle\int_0^1 \frac{t^{μ-1}-t^{v-1}}{1-t}dt=\frac{1}{2}\{ψ(v)-ψ(μ)\}\\
\end{alignat}以上より$$\displaystyle\int_0^{\frac{π}{4}} (\cos^{μ-1} 2x-\cos^{v-1} 2x)\cos xdx=\frac{1}{2}\{ψ(v)-ψ(μ)\}$$








\((3)\) \(\sin x=t\) と置きます。\((\cos xdx=dt)\)$$\displaystyle\int_0^{\frac{π}{2}}\frac{\sin^{μ-1}x -\sin^{v-1} x}{\cos x}dx=\displaystyle\int_0^1 \frac{t^{μ-1}-t^{v-1}}{1-t^2}dt$$\(t^2=s\) と置きます。\((2tdt=ds)\)$$=\displaystyle\int_0^1 \frac{s^{\frac{μ-1}{2}}-s^{\frac{v-1}{2}}}{1-s}\cdot \frac{1}{2\sqrt{s}}ds=\frac{1}{2}\displaystyle\int_0^1 \frac{s^{\frac{μ}{2}-1}-s^{\frac{v}{2}-1}}{1-s}ds=\frac{1}{2}\left\{ψ\left(\frac{v}{2}\right)-ψ\left(\frac{μ}{2}\right)\right\}$$以上より$$\displaystyle\int_0^{\frac{π}{2}}\frac{\sin^{μ-1}x -\sin^{v-1} x}{\cos x}dx=\frac{1}{2}\left\{ψ\left(\frac{v}{2}\right)-ψ\left(\frac{μ}{2}\right)\right\}$$









\((4)\) \(\cos x=t\) と置きます。\((-\sin xdx=dt)\)$$\displaystyle\int_0^{\frac{π}{2}}\frac{\cos^{μ-1}x -\cos^{v-1} x}{\sin x}dx=\displaystyle\int_1^0 \frac{t^{μ-1}-t^{v-1}}{1-t^2}(-dt)=\displaystyle\int_0^1 \frac{t^{μ-1}-t^{v-1}}{1-t^2}dt$$\(t^2=s\) と置きます。\((2tdt=ds)\)$$=\displaystyle\int_0^1 \frac{s^{\frac{μ-1}{2}}-s^{\frac{v-1}{2}}}{1-s}\cdot \frac{1}{2\sqrt{s}}ds=\frac{1}{2}\displaystyle\int_0^1 \frac{s^{\frac{μ}{2}-1}-s^{\frac{v}{2}-1}}{1-s}ds=\frac{1}{2}\left\{ψ\left(\frac{v}{2}\right)-ψ\left(\frac{μ}{2}\right)\right\}$$以上より$$\displaystyle\int_0^{\frac{π}{2}}\frac{\sin^{μ-1}x -\sin^{v-1} x}{\cos x}dx=\frac{1}{2}\left\{ψ\left(\frac{v}{2}\right)-ψ\left(\frac{μ}{2}\right)\right\}$$

コメントを残す

メールアドレスが公開されることはありません。 * が付いている欄は必須項目です